AB0378 Anti-Drug Antibody (ADAB) Differentially Affect Response among Specific TNFI and Also among Diseases: an SLR and Meta-Analysis. (10th June 2014) - Borazan, N.; Thomas, S.; Barroso, N.; Duan, L.; Furst, D.E.
Abstract : Background: Immunogenicity to TNFi as a class is moderately common but no comparisons among TNFi -specific immunogenicity have been made, nor is it known whether these TNFi -specific ADAB differentially effected response among the TNFi. Further, it is possible that ADAB may differ among diseases and may differentially affect response. Objectives: To examine TNFi- specific ADAB and to examine whether these drug-specific ADAB change response differently across TNFi. Further, to examine whether immunogenicity is different among RA, spondyloarthritis (SPA) and inflamm. bowel disease (IBD) and differentially affects disease response. Methods: A systematic literature review used Pubmed, Web of Science and the Cochrane Library from 1966 to 12/1/12. Inclusion criteria: English; randomized controlled trials-observational trials- case reports (>5 pts); ≥18 yrs. Exclusions: no clinical correlates: cancer<5 yrs before the study; renal dialysis. Double extraction was followed by a third extraction if there were disagreements. Random effect models estimated the effects of ADAB on TNFi response, by drug and by disease. ANOVA tested differences among TNFi and diseases. Results: 9955 patients from 48 studies were examined. Trial durations:8 to 469 wks- median: 46 wks. Overall, ADAB were detected in 17% (range: 13-21%). Table 1 shows that ADAB statistically decreased response to TNFi (p=0.04), driven by adalimumab (adal) (RR=0.35) and infliximab (IFX) (RR=0.46). In by-drug comparisons, there were only numerical differences between etanercept (ETA) vs adal. (p=0.07) and golimumab (GOL). vs adal. (p=0.09). Concomitant immunosuppressives did not statistically significantly ameliorate ADAB overall (p=0.82) (Table 1 ). This result is complex, however, as immunosuppressives statistically significantly ameliorated the ADAB responses to IFX (RR=0.64) and adalimumab (RR=0.63), had a marginal effect on ADAB engendered by GOL (RR=0.93, 95%CI [0.86, 1.01]) and had no effect on the production of ADAB to ETA or certolizumab (CZP). The percentages of ADAB by disease varied: 7%>SpA, 13%>RA, 25%> IBD. They were statistically significant for all 3 diseases but the differences between diseases were marginal (p=0.06) (Table 2 ). ADAB statistically decreased responses to TNFi in RA (RR=0.49)and SPA (RR=0.45) although, overall, there were no differences among the diseases (p=0.66). Immunosuppressives partially abrogated the ADAB-engendered decrease in response for all 3 diseases: RA (RR=0.78), IBD (RR=0.63), SpA (RR=0.32)- all statistically significant, with no differences among diseases (p=0.33). Results: There are differential degrees of ADAB among drugs and, to a marginal degree, between diseases. These ADAB effect responses to some biologics and for all 3 diseases. Also immunosuppressives abrogate the ADAB for IFX and adal. Except for these, there are no statistical differences when comparing drugs and diseases, possibly because there is heterogeneity among studies resulting in wide 95% confidence limits. Disclosure of Interest: N. Borazan: None declared, S. Thomas: None declared, N. Barroso: None declared, L. Duan: None declared, D. Furst Grant/research support: AbbVie, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, BMS, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: AbbVie, Actelion, UCB DOI: 10.1136/annrheumdis-2014-eular.3415